Effectiveness of silver diamine fluoride 38% on reduction of gingivitis in dogs: a randomized clinical trial - Kern, Amarett; Renteria, Tammy (White); Rothen, Marilynn L.; Mancl, Lloyd A.; Milgrom, Peter (Frontiers in Veterinary Science, 2023)
Periodontal disease is a ubiquitous disease in small animal veterinary medicine. Currently regular professional dental cleaning and daily tooth brushing are considered gold standards in the prevention of periodontal disease. Efforts to find a noninvasive, cost effective and easy to use preventative for periodontal disease are ongoing. The primary objective of this double-blind randomized clinical trial was to determine if a single application of silver diamine fluoride (SDF) 38% on the buccal surface of all teeth would reduce gingivitis within three months in dogs with stage two periodontal disease. Twenty-nine client-owned dogs 3-12 years old, 6-35 pounds were randomized 1:1 into active and placebo-control groups. Both groups underwent a baseline treatment and a three-month follow-up under general anesthesia. Gingival Index (GI), Plaque Index (PI), and Calculus Index (CI) were assessed and recorded at each event. A single application of SDF 38% did not significantly lower GI relative to the control group. However, the GI score dropped significantly in both groups relative to baseline, with a 53% reduction in the average GI score for dogs that received SDF 38% treatment and a 44% reduction for dogs that received placebo treatment. There were no differences in PI or CI scores compared to control groups. Further research is needed to determine if a more frequent application or a longer study duration would yield a different outcome.